Poligami dalam Perspektif Teori Batas (Studi Pemikiran Muhammad Shahrur) - Nuru Asiya Nadhifah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2007)
This article describes polygany in the perspective of Limit Theory of Muhammad Shahrur. Polygamy is an issue of islamic law which create controversy among Muslim community. In al-Qur’an, the only verse dealing with polygamy is al-Nisa: 3. Using the limit theory (nazariyyah al-hudud) of Muhaamad Shahrur the verse produces two kinds of limit; the limit of quantity (hadd fi al-kamm) and the limit of quality(hadd fi al-kaif). From the analysis on the foundation of Shahrur’s thought on polygamy, it is apparent that he emphasizes on the protection of orphans because they must be protected and fed. This condition, according to Shahrur, indicates validity of polygamy on the importance of taking cares of orphans towards those who no longer have fathers.